Complexes of DNA bases and Watson–Crick base pairs interaction with neutral silver Agn (n = 8, 10, 12) clusters: a DFT and TDDFT study. Issue 4 (12th March 2018) - Srivastava, Ruby
Abstract : We study the binding of the neutral Agn ( n  = 8, 10, 12) to the DNA base-adenine (A), guanine (G) and Watson–Crick –adenine-thymine, guanine-cytosine pairs. Geometries of complexes were optimized at the DFT level using the hybrid B3LYP functional. LANL2DZ effective core potential was used for silver and 6–31 + G ** was used for all other atoms. NBO charges were analyzed using the Natural population analysis. The absorption properties of Agn –A, G/WC complexes were also studied using time-dependent density functional theory. The absorption spectra for these complexes show wavelength in the visible region. It was revealed that silver clusters interact more strongly with WC pairs than with isolated DNA complexes. Furthermore, it was found that the electronic charge transferred from silver to isolated DNA clusters are less than the electronic charge transferred from silver to the Agn –WC complexes. The vertical ionization potential, vertical electron affinity, hardness, and electrophilicity index of Agn –DNA/WC complexes have also been discussed. Abstract :